If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + 5) = 63 Reorder the terms: x(5 + x) = 63 (5 * x + x * x) = 63 (5x + x2) = 63 Solving 5x + x2 = 63 Solving for variable 'x'. Reorder the terms: -63 + 5x + x2 = 63 + -63 Combine like terms: 63 + -63 = 0 -63 + 5x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '63' to each side of the equation. -63 + 5x + 63 + x2 = 0 + 63 Reorder the terms: -63 + 63 + 5x + x2 = 0 + 63 Combine like terms: -63 + 63 = 0 0 + 5x + x2 = 0 + 63 5x + x2 = 0 + 63 Combine like terms: 0 + 63 = 63 5x + x2 = 63 The x term is 5x. Take half its coefficient (2.5). Square it (6.25) and add it to both sides. Add '6.25' to each side of the equation. 5x + 6.25 + x2 = 63 + 6.25 Reorder the terms: 6.25 + 5x + x2 = 63 + 6.25 Combine like terms: 63 + 6.25 = 69.25 6.25 + 5x + x2 = 69.25 Factor a perfect square on the left side: (x + 2.5)(x + 2.5) = 69.25 Calculate the square root of the right side: 8.321658489 Break this problem into two subproblems by setting (x + 2.5) equal to 8.321658489 and -8.321658489.Subproblem 1
x + 2.5 = 8.321658489 Simplifying x + 2.5 = 8.321658489 Reorder the terms: 2.5 + x = 8.321658489 Solving 2.5 + x = 8.321658489 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2.5' to each side of the equation. 2.5 + -2.5 + x = 8.321658489 + -2.5 Combine like terms: 2.5 + -2.5 = 0.0 0.0 + x = 8.321658489 + -2.5 x = 8.321658489 + -2.5 Combine like terms: 8.321658489 + -2.5 = 5.821658489 x = 5.821658489 Simplifying x = 5.821658489Subproblem 2
x + 2.5 = -8.321658489 Simplifying x + 2.5 = -8.321658489 Reorder the terms: 2.5 + x = -8.321658489 Solving 2.5 + x = -8.321658489 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2.5' to each side of the equation. 2.5 + -2.5 + x = -8.321658489 + -2.5 Combine like terms: 2.5 + -2.5 = 0.0 0.0 + x = -8.321658489 + -2.5 x = -8.321658489 + -2.5 Combine like terms: -8.321658489 + -2.5 = -10.821658489 x = -10.821658489 Simplifying x = -10.821658489Solution
The solution to the problem is based on the solutions from the subproblems. x = {5.821658489, -10.821658489}
| 3(7-2v)+1=-5(v-2) | | x^2+5x=2+3x-24 | | (168/7)3^2-4^3 | | 5(x+3)=2x+3 | | c+c=-5 | | -6+3x+2x-11=13 | | 5*-18-4x=-36 | | -30/(-6)= | | 2x^2+31x-8.5=0 | | -8+n=n-6 | | 2x-6=3x-1-x-7 | | 3/3=9/10k | | g(x)=-2x^2+8x-16 | | Y+5(-1)=0 | | 2u^2-17u-9= | | 7-4y=3-5y | | -32-7n=-6(2+4n)-3 | | 5x-x-6=58 | | 4x^2=3x+12 | | 4v^2-5v+1= | | X+14+x+5=11 | | c^2/2- | | p/12-8=9 | | -(-8n-4)+6=12+6n | | (x^2-10x-24)/(5x^3-20x) | | Y+5(1)=0 | | 30-r=-8 | | 16×10/3 | | p/12-9=-9 | | 4x+3+3=7x | | 14+11x+55=19x+5 | | 5.6/0.4 |